Stroop performance of partially sleep-deprived healthy volunteers at simulated hypobaric hypoxia condition - Sudhanshu Shekhar Mohapatra; Deepak Kumar Khukhar; Seema Gambhir; Harshavardhan Gandikota; AVK Raju; Ranjan Sarkar; Sachin Bharadwaj (Indian Journal of Aerospace Medicine, 2026)
Objectives: The amount of average nightly sleep that the military aircrew gets is 6 h, which is 2 h less than the optimal sleep of 8 h. With the background that the executive type of cognitive functions, which are critical to flight operations, deteriorate under hypoxic conditions, it was a purposeful initiative to undertake the study to determine if the cognitive dysfunction related to executive functions is further deteriorated by 2 h of partial sleep deprivation (PSD) or not. Material and Methods: The experiment was carried out on 25 healthy participants on two occasions, i.e., on the day after an optimal sleep and on the day after 2 h of sleep deprivation at three different pressure altitudes, i.e., ground level, 10,000 ft and 18,000 ft in a hypoxia simulator explosive decompression chamber. The Stroop test was selected from the psychological test battery called Psychomotor Evaluation Designed for Aviators (pSuMEDhA) developed at the Institute of Aerospace Medicine. SpO2 was measured using a finger pulse oximeter. Two-way ANOVA was conducted to compare the means. Results: “Altitude” effect in the form of statistically significant fall of mean SpO2 from average ground level values of (Day-1 and Day-2) 97.8% and 98% to 92.1% and 92.6% at 10,000 ft, and 79.1% and 78.9% at 18,000 ft was observed. Similarly, a statistically significant increase of mean Stroop time (ST) from an average ground-level value of 11.04 and 11.92 to 19.08 and 26.36 at 10,000 ft and 43.28 and 55.68 at 18,000 ft was observed on both days. However, there was neither the “Day” effect nor the “Interaction (Day Altitude)” effect. Conclusion: ST, which is the indicator of cognitive difficulty, was higher at 18,000 ft in comparison to the ST recorded at ground and at 10,000 ft observed on the day after optimal sleep and also on the day after 2 h of PSD. When ST at different levels of altitude was compared, the values recorded on Day-2 were not statistically different from the values recorded on Day 1, implying similar cognitive difficulty. The accentuation effect of “Two hours PSD” on cognitive performance under hypoxia condition could not be established through Stroop testing.